TEACHING THE SPECIFIC FEATURES OF VOCABULARY IN NEWSPAPER HEADLINES - Iļjina, Svetlana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The present research deals with the variety of lexical items used in newspaper headlines in British press. The report discusses teaching strategies how to develop readers’ vocabulary competence and its influence on the overall comprehension of the meaning implied in the headline. The study touches upon the strategy of direct explanation of new vocabulary, morphemic analysis of words, and stylistic analysis of the phraseological units used in newspaper headlines. The research emphasizes the role of emotively coloured vocabulary in the formation of attractive headlines.